﻿An in silico investigation of 1,2,4-triazole derivatives as potential antioxidant agents using molecular docking, MD simulations, MM-PBSA free energy calculations and ADME predictions - Yevhen Karpun; Sergiy Fedotov; Anastasiia Khilkovets; Yuriy Karpenko; Volodymyr Parchenko; Yana Klochkova; Yuliia Bila; Iryna Lukina; Natalia Nahorna; Volodymyr Nahornyi (Pensoft Publishers, 2023)
In this study, we've performed computable studies of previously synthesized 1,2,4-triazole derivatives by virtual screening due to antioxidant activity. Six enzymes responsible for regulating oxidative stress were selected as key targets. One hundred and twelve compounds were subjected to semi-flexible molecular docking, which resulted in the selection of 23 substances based on binding energy for further ADME analysis. In addition, molecular dynamics studies of complexes with the best docking scores, reference complexes and apo-proteins were described in detail here. The results of 100 ns modeling (RMSD, RMSF, SASA, Rg, PCA) indicate great stability during the formation of complexes with our two potential compounds, as well as favorable binding energy, which was determined theoretically by means of the MM/PBSA method, thereby increase the likelihood of their acting as promising inhibitors of selected enzymes.